Pravo in pravniki, zlasti odvetniki, na družbenem omrežju v Avstriji - Zenz, Matej (Podjetje in delo, 2024)
The article explores the role and challenges of social media usage by lawyers in Austria. It emphasises that social media platforms like Facebook, Twitter, LinkedIn, and Instagram offer new opportunities for communication, advertising, and networking, but also significant challenges regarding data protection, confidentiality, and ethical standards. In Austria, the use of social media is regulated by various laws, including the General Data Protection Regulation (GDPR), the Telecommunications Act, the E-Commerce Act, and the Law on Combating Hate on the Internet. These laws ensure the protection of users' rights and impose the duty on social media operators to ensure data security. For lawyers, social media also presents numerous legal challenges and opportunities. Contract law specialists deal with terms of use, content ownership, behavior rules, and liability exclusions. An important aspect is also representing influencers and resolving disputes regarding advertising and unfair competition. Lawyers must adhere to strict professional rules when using social media to maintain integrity and trust in the legal profession. These regulations include advertising restrictions that must be truthful, factual, and in line with the profession's honor. Examples of using different platforms like X (formerly Twitter), Facebook, Instagram, TikTok, YouTube, and LinkedIn illustrate how lawyers can use these channels for communication, sharing professional content, and advertising their services. The article also highlights the importance of social media in legal proceedings, where media reports live from courtrooms via platforms like X, allowing broader public access to proceedings. Concluding that social media has become an indispensable part of the legal profession, the author encourages lawyers to use it to their advantage, but responsibly and ethically.
Keywords: Družbena omrežja (internet); Odvetniki